Plastic Pollution Research in Indonesia: State of Science and Future Research Directions to Reduce Impacts - Vriend, Paul; Hidayat, H.; van Leeuwen, J.; Cordova, M. R.; Purba, N. P.; Löhr, A. J.; Faizal, I.; Ningsih, N. S.; Agustina, K.; Husrin, S.; Suryono, D. D.; Hantoro, I.; et al. (Frontiers in Environmental Science, 2021)
Several studies have suggested Indonesia to be among the top plastic polluting countries globally. Data on the presence and amounts of plastic pollution are required to help design effective plastic reduction and mitigation strategies. Research quantifying plastic pollution in Indonesia has picked up in recent years. However, a lack of central coordination in this research has led to research output with different goals, methods, and data formats. In this study we present a meta-analysis of studies published on plastic pollution in Indonesia to uncover gaps and biases in current research, and to use these insights to suggest ways to improve future research to fill these gaps. Research gaps and biases identified include a clear preference for marine research, and a bias towards certain environmental compartments within the marine, riverine, and terrestrial systems that have easy to apply methods. Units of measurement used to express results vary greatly between studies, making it difficult to compare data effectively. Nevertheless, we identify polypropylene (PP) and polyethylene variants (PE, HDPE, LDPE) to be among the most frequently found polymers in both macro- and microplastic pollution in Indonesia, though polymer identification is lacking in a large part of the studies. Plastic research is mostly done on Java Island (49 studies, 59%). We recommend research methods used to quantify plastic pollution to be harmonized. Moreover, we recommend a shift in focus of research towards the riverine and terrestrial environments and a shift of focus of environmental compartments analyzed within these systems, an increase in spatial coverage of research across Indonesia, and lastly, a larger focus on polymer characterization. With these changes we envision future research which can aid with the design of more effective and targeted reduction and mitigation strategies.